Broadband Continuum Generation in Single-Mode Optical Fiber - Maraña, B. D.; Gabayno, J. F.; Garcia, W. O. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
We report broadband continuum generation in a single-mode step-index optical fiber pumped by the second harmonic (532 nm) of a Nd:YAG laser. The continuum started to appear together with the first-order Stokes at 545 nm with an input power of 11 mW. The appearance of the second-order Stokes is distinctly observed at 557.5 nm for 96 mW input power. The generated continuum spans 123.12 THz (550–712 nm). Asymmetric cross-phase modulation-induced spectral sidebands were also observed.